Estrategias de afrontamiento utilizadas en adultos mayores con soledad - Chamba Rosillo, Nashely Guadalupe (2024)
Loneliness in the elderly people has become an increasing concern in many areas, from psychological to the socio- health. This is because its important impact in the emotional well-being and quality of life of this population. This research aimed to determine the most recent scientific evidence related to facing strategies in lonely elderly, to identify these strategies, to discover the function it has in this demographic group and to design a promoting plan addressed to them. This plan is based on the identified facing strategies. For the development of this research, a mixed nonexperimental, cross-sectional approach was used, with a descriptive and bibliographic scope and the bibliographic synthesis method was used. The study population included the scientific literature available in databases such as: Science Direct, Pubmed, Dialnet, Scopus, Scielo and Redalyc, and selection criteria were applied, forming a sample that included 15 documents, 10 qualitative and 5 quantitative. Results revealed that older adults experiencing loneliness employ a variety of strategies, highlighting individual and social approaches, such as institutional planning, religious strategies, seeking social support, active coping, use of technology, and individual practices. These strategies were shown to be effective in attenuating the perception of loneliness, thus highlighting the role of these strategies in the goal readjustment and substitution. In this way, it was concluded that elderly use a variety of strategies to confront loneliness, highlighting its importance in emotional and social well-being